Pemberian Fasilitas Ekspor Crude Palm Oil Oleh Dirjen Perdagangan Luar Negeri Ditinjau dari Undang – Undang Tindak Pidana Korupsi - I Kadek Yukik Okta Dwipayana; I Nyoman Gede Sugiartha; I Nyoman Sujana (Warmadewa Press, 2023)
The state of Indonesia is a country that has a rich culture besides that the number of its people's population which is increasing every day makes a lot of different thoughts for each person with their respective life goals. As a country of law, Indonesia has several components that specifically explore the law itself, starting from its regulation to its sanctions which make people's behavior limited by law and on the other hand with the existence of community laws become more controlled and reduce behavior that violates the norms carried out. The research conducted by the author is related to corruption crimes where corruption itself is carried out by an official who has certain authority in his field and has the full trust of the government and because of his authority makes it easier to carry out actions that harm the nation and state.